DIMENSI INTERNASIONAL DALAM DEFORESTASI DI INDONESIA - Sisilia Asri . (Universitas Wahid Hasyim Semarang, 2013)
Abstract This paper describes about the involvement of international actors in deforestation in Indonesia. These international actors are classified into two main actor that are International Fund institutions and International creditors. International actors involved in deforestation started when Indonesia passed out the foreign investment policy, which allows any kinds of investment operate in Indonesia development and economic activities. These policies resulted and become Indonesian foreign debts. Private debts to the International creditors such as ECA (Export Credit Agency), in fact was not able to be repaid by the logging companies punctually. These cases were seen in PT. RAPP and PT Indah Kiat debts. Beside those factors above, decentralization of forest management which was started on 2001 resulted in contra productive policies due to insufficient law and legal instrument to accommodate the low enforcement of sustainable development in forestry sector As the solution for private debts, Indonesia government received loan from International donor such as CGI, IMF and World Bank. Those international donors imposed some structural adjustment programs and pushed Indonesia’s economic more liberal. This policy return in further exploitation of Indonesia’s forest and again resulted in deforestation. Key words : deforestation, International donors, International creditors, Foreign Debts